1998
DOI: 10.2527/1998.761299x
|View full text |Cite
|
Sign up to set email alerts
|

A review of bloat in feedlot cattle.

Abstract: Improvements in feedlot management practices and the use of various feed additives have reduced, but not eliminated, the occurrence of bloat in feedlot cattle. Feedlot bloat reduces the profitability of production by compromising animal performance and more directly by causing fatalities. In feedlots, bloat is associated with the ingestion of large amounts of rapidly fermented cereal grain and destabilization of the microbial populations of the rumen. An abundance of rapidly fermented carbohydrate allows acid-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
76
1
9

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(87 citation statements)
references
References 0 publications
1
76
1
9
Order By: Relevance
“…Whereas the colonies on TH-glucose medium were small and nonshiny, they were extremely mucoid on medium supplemented with sucrose. This suggests that the glucans produced by these glycosyl transferases represent the mucopolysaccharides produced during feedlot bloat in cattle (14). Thus, among streptococci, S. gallolyticus is the only one known to produce both a capsule and a mucoid extracellular glucan.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas the colonies on TH-glucose medium were small and nonshiny, they were extremely mucoid on medium supplemented with sucrose. This suggests that the glucans produced by these glycosyl transferases represent the mucopolysaccharides produced during feedlot bloat in cattle (14). Thus, among streptococci, S. gallolyticus is the only one known to produce both a capsule and a mucoid extracellular glucan.…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that the production of mucopolysaccharides by S. bovis increases the viscosity of ruminal fluid and stabilizes the foam implicated in frothy feedlot bloat (14). A second locus identified in the UCN34 genome encodes three different glycosyl transferases where each structural gene is associated with a regulatory gene (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of treatment for bloat in the present study (2 to 5%) would likely have been reduced if ionophores had been included in the diet (Galyean and Rivera 2003), but the presence of monensin in diets would have confounded the observed responses to the other subtherapeutic antimicrobials administered. Feedlot mortalities due to bloat have been estimated at between 0.1 and 0.2% in western Canada (Merrill 1994), although incidence of bloat is thought to be site dependent due to variations in bunk management, diet, grain processing and animal type (Cheng et al 1998).…”
Section: Animal Healthmentioning
confidence: 99%
“…Another effect of intense proliferation of Streptococcus and protozoa in the rumen is the production of mucopolysaccharides, which increases ruminal fluid viscosity and may cause bloat (BERGEN;BATES, 1984). Ionophores acts reducing the population of these bacteria; however, they do not have an effect over the types of bacteria that use lactic acid produced through rumen fermentation, such as Selenomonas ruminantium, thus controlling the occurrence and severity of conditions such as acidosis and bloat (CHENG et al, 1998).…”
Section: Introductionmentioning
confidence: 99%